THE ABILITY TO ADJUST SELF, WORK ACHIEVEMENT ON WORK SATISFACTION MEDIATED BY WORK ENGAGEMENT AMONG EMPLOYEES OF PT PERTAMINA IN BEKASI REGENCY - Annisa Fitri Weni, Desiam; Purwani Setyaningrum, Retno (Magister Manajemen Universitas Islam Malang, 2025)
This research is expected to contribute to the development of human resource management theory, especially in the Ability to Adjust Self, Work Achievement to Work Satiscation in Work Engagement mediation. Data analysis was carried out using Structural Equation Modeling (SEM) techniques with the help of software AMOS. The respondents in this study are PT Pertamina employees who work in various divisions with a sample number determined using the Slovin formula, which is 150 employees randomly selected from the existing population. The test results showed that the ability to adjust self did not have a significant direct effect on job satisfaction. Work achievement also does not have a significant effect directly on job satisfaction. The ability to adjust has been proven to have a positive and significant influence on work engagement. Work engagement has a positive and significant influence on job satisfaction. The results of this study can be a reference for the management of PT Pertamina, that Adaptability, Work Achievement, Work Attachment, and Job Satisfaction have a very important role in increasing employee job satisfaction. Companies also need to regularly monitor and evaluate the development of employee job attachment and job satisfaction to achieve optimal results.